2005
DOI: 10.1086/432119
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides brasiliensis Disseminated Disease in a Patient with Inherited Deficiency in the  1 Subunit of the Interleukin (IL)-12/IL-23 Receptor

Abstract: This unique observation supports previous studies of PCM suggesting that IL-12, IL-23, and IFN-gamma play an important role in protective immunity to P. brasiliensis. Tuberculosis and PCM are thus not only related clinically and pathologically, but also by their immunological pathogenesis. Our study further expands the spectrum of clinical manifestations of inherited defects of the IL-12/IL-23-IFN-gamma axis. Patients with unexplained deep fungal infections, such as PCM, should be tested for defects in the IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 38 publications
0
62
0
1
Order By: Relevance
“…These combined immunological defects leave IL12RB1 mut individuals more susceptible to infection by mycobacteria, Salmonella, and Candida species, as reported in a recent extensive international study (20). Smaller and more regional studies have also shown positive associations between IL12RB1 deficiencies (13,14,21,23,(51)(52)(53) or IL12RB1 polymorphisms (16,22,(54)(55)(56)(57) and susceptibility to a number of other maladies and infectious diseases. However, notably, beneficial IL12RB1 polymorphisms also have been discovered (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…These combined immunological defects leave IL12RB1 mut individuals more susceptible to infection by mycobacteria, Salmonella, and Candida species, as reported in a recent extensive international study (20). Smaller and more regional studies have also shown positive associations between IL12RB1 deficiencies (13,14,21,23,(51)(52)(53) or IL12RB1 polymorphisms (16,22,(54)(55)(56)(57) and susceptibility to a number of other maladies and infectious diseases. However, notably, beneficial IL12RB1 polymorphisms also have been discovered (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Deficient production of certain cytokines, such as IFN-γ, IL-12, and IL-23, as well as of their receptors, predisposes patients to TB and to PCM. (5) The pattern of cytokine production by CD4 + T lymphocytes can determine the severity of the clinical profile of these two diseases. The predominance of IFN-γ (produced by CD4 + T lymphocytes known as T helper 1 cells) is generally associated with a more favorable clinical evolution, whereas the predominance of IL-4, IL-5, and IL-10 (produced by CD4 + T lymphocytes designated T helper 2 cells) results in a more severe disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…(3,4) Deficient production of certain cytokines, such as interleukin (IL)-12, IL-23, and interferon gamma (IFN-γ), as well as of their receptors, predisposes patients to TB and to PCM. (5) Since the clinical presentation of these diseases can be similar, it has been observed that several patients definitively diagnosed with PCM had been previously treated for TB, although without sputum smear microscopy confirmation. Most of those patients did not respond to specific anti-TB treatment and only improved after drug treatment for PCM had been started.…”
Section: Introductionmentioning
confidence: 99%
“…The defect is a result of an interstitial deletion that creates a signal-impaired but cell-surfacepersisting molecule that exerts a dominant-negative effect on IFN-g cellular responses of the wild-type receptor. Furthermore, coccidioidomycosis, histoplasmosis, paracoccidioidomycosis and cryptococcosis have been reported in patients with missense homozygous or heterozygous mutations in the b1 subunit of IL-12R (Moraes-Vasconcelos et al 2005;Rezai et al 2008;de Beaucoudrey et al 2010;Vinh et al 2011). Although cellular responses to IFN-g are unaffected in these patients, IL-12-dependent IFN-g production is impaired.…”
Section: Disorders In Cytokine Signaling Il-12/ifn-g Signalingmentioning
confidence: 99%